10/#1040 Fertility-sparing surgery in stage I ovarian dysgerminoma – the role of surgical and radiological staging. (4th December 2022) - Vicini, Debora; Fumagalli, Diletta; Grassi, Tommaso; Sina, Federica; Giuliani, Daniela; Bonazzi, Cristina Maria; Marchette, Martina Delle; Marino, Giuseppe; Testa, Filippo; Boccadutri, Mariaclara; Negri, Serena; Landoni, Fabio; et al.
Abstract : Objectives: To evaluate the oncologic outcome of surgical and radiological staging in patients diagnosed with stage I ovarian dysgerminoma who underwent a fertility-sparing surgery in a tertiary-care center in Monza, Italy. Methods: We performed a retrospective, observational study of women with a histologically confirmed diagnosis of ovarian dysgerminoma referred to our Institution from 1980 to 2020. We collected patients' characteristics, surgical procedures, postoperative management, disease recurrence rate, disease-free survival, and overall survival rates. Descriptive statistics were performed for baseline characteristics, while Fisher's exact test was used to investigate the association between staging methods and recurrent disease. P<0.05 was considered significant. Results: Of 131 patients diagnosed with ovarian dysgerminoma, 79 were diagnosed with early-stage disease and treated with fertility-sparing surgery. Forty-seven patients received intraperitoneal only or intraperitoneal plus retroperitoneal staging, while 32 were staged with imaging only. In the first group, one patient relapsed (2%), while 7 in the second group (22%) (p<0.05). No difference in recurrence rate was found between patients managed with intraperitoneal staging only (1/24) and with intraperitoneal plus retroperitoneal staging (0/23). Overall survival was similar in the surgical and radiological staging subgroups, with a five-year survival rate of 100% (median follow-up of 9.5 years). Conclusions: Fertility-sparing surgical treatment is safe and feasible for patients with early-stage ovarian dysgerminoma. Surgical staging may reduce disease recurrence compared to nonsurgical staging. However, overall survival is not affected by the staging method.